Analisis Lean Process Menggunakan Metode Value Stream Mapping Pada Proses Incoming Material Di PT Sat Nusapersada Tbk - Angel Aurora Butar Butar (Journal of Collaborative Industrial Management (JCIM), 2026)
PT Sat Nusapersada is an electronics manufacturing company that produces various electronic products such as smartphones, laptops, tablets, network switches, routers, Wi-Fi modules, smartwatches, and PCBs. This study aims to determine the types of waste that occur in the incoming material process using a lean approach and the Value Stream Mapping (VSM) method at PT Sat Nusa Persada Tbk. The incoming material process, which is the starting point in the company's supply chain, was found to have several inefficiencies such as long waiting times, activities that do not provide added value, and suboptimal division of labor. Through interviews, observations, and root cause analysis using the 5W + 1H and 5 Why Analysis methods, it was found that the total process time reached 9,100 seconds with a PCE value of 63.08%. After analysis and the preparation of a future state map based on proposed improvements, the total process time decreased to 6,480 seconds and the PCE value increased by 13.89% to 76.97%.